Locus Of Control Meningkatkan Kinerja Pegawai Persepsi Dukungan Organisasi Meningkatkan Keterikatan Pegawai - Nafila Rizqu Latifa; Sih Darmi Astuti (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of locus of control and perceptions of organizational support on employee performance with employee engagement and proactive work behavior as intervention variables in DP3AP2KB Central Java Province. This study uses a quantitative descriptive which describes the condition of the facts with the data collected from a questionnaire based on direct observation of the Central Java Province DP3AP2KB. The population in the study included all DP3AP2KB Central Java Province workers, totaling 101 workers and the analysis technique used was multiple linear regression analysis, using SPSS Version 24, and it was found that locus of control had the strongest influence on improving employee performance. Perceived organizational support will also improve employee performance through proactive behavior of employees, because perceived organizational support is found to be unable to directly influence employee performance.